# SOLUTION: plotting ordered pairs so that each is a solution for the given equation: This is my problem 3x+4y=12 (0, ) ( ,3/4) ( ,0) (8/3, ) I have spent about 4 hours working on this. I tr

Algebra ->  Algebra  -> Coordinate-system -> SOLUTION: plotting ordered pairs so that each is a solution for the given equation: This is my problem 3x+4y=12 (0, ) ( ,3/4) ( ,0) (8/3, ) I have spent about 4 hours working on this. I tr      Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Coordinate systems, graph plotting, etc Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Coordinate-system Question 69430This question is from textbook Beginning Algebra : plotting ordered pairs so that each is a solution for the given equation: This is my problem 3x+4y=12 (0, ) ( ,3/4) ( ,0) (8/3, ) I have spent about 4 hours working on this. I tried solving for both x and y then plugging the number in. That didnt work out. I have tried graphing it to see if I could make more sense out of it that way, and that didnt help me much, and I believe it confused me worse. PLease Help!!This question is from textbook Beginning Algebra Found 2 solutions by stanbon, tutorcecilia:Answer by stanbon(57290)   (Show Source): You can put this solution on YOUR website!This is my problem 3x+4y=12 (0, ) ( ,3/4) ( ,0) (8/3, ) If x=0, you get 0+4y=12; y=3. So the point is (0,3) If x=8/3, you get 3(8/3)+4y=12; 8+4y=12; 4y=4; y=1. So the point is (8/3,1) If y=3/4, you get 3x+4(3/4)=12; 3x+3=12; 3x=9; x=3. So the point is (3,3/4) If y=0, you get 3x+0 = 12; x=4. So the point is (4,0) ------------ Cheers, Stan H. Answer by tutorcecilia(2152)   (Show Source): You can put this solution on YOUR website!3x+4y=12 [solve for y] 3x-3x+4y=-3x+12 4y=-3x+12 4y/4=-3x/4+12/4 y=-3/4x+3 [this is the equation of the line. from here, plug-in the known variable and solve for the missing variable] . y=-3/4x+3 (let x=0 and solve for y] y=-3/4(0)+3 y=0+3 y=3 (0,3) . y=-3/4x+3 (let y=3/4 and solve for x] 3/4=-3/4x+3 3/4-3=-3/4x+3-3 -9/4=-3/4x (-9/4)(-4/3)=x 3=x (3, 3/4) . y=-3/4x+3 (let y=0 and solve for x] 0=-3/4x+3 -3=-3/4x (-4/3)(-3/1)=-3/4x(-4/3) 4=x (4,0) . y=-3/4x+3 (let x=8/3 and solve for y] y=-3/4(8/3)+3 y=-2+3 y=1 (8/3, 1)